An Experimental Investigation of the Factors Affecting Client Contentment in the Banking Sector (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The basic objective of this research is to identify the variables that manipulate consumer happiness in the Indian banking industry because a nation's ability to expand economically and maintain stability depends on how strong its banking system is. The goal of the research is to examine and evaluate the impact of client happiness on the level of service in the banking industry. Data was gathered from 382 participants who were clients of 32 chosen banks in India as a representative group. The necessary data and information were gathered using an alreadystructured questionnaire. Data were analyzed using the OLS regression model and explanatory statistical techniques. The findings of this study demonstrate that client happiness is statistically significantly impacted by the excellence of the examination (e.g., dependability, and compassion). The findings also indicate a favorable relationship between satisfaction with service and other parameters in India's banking industry. As per the outcomes of the present research, customer satisfaction in the domestic banking sector is significantly influenced by the service quality aspects of tangibility, dependability, and empathy. The results of this study point to the need for Bank Supervisory Power, Central Bank of India, and bank executives to place a high priority on ensuring the highest level of customer satisfaction